Bioenergetic influence on the historical development and decline of industrial fisheries. (10th May 2020) - Guiet, J; Galbraith, E D; Bianchi, D; Cheung, W W L
Abstract: The global wild capture fishery expanded rapidly over the 20th century as fishing technology improved, peaking in the 1990s as most fisheries transitioned to fully- or over-exploited status. Historical records for individual large marine ecosystems (LMEs) tend to echo this same progression, but with local variations in the timing and abruptness of catch peaks. Here, we provide objective descriptions of these catch peaks, which generally progressed from high- to low-latitude LMEs, and attribute the temporal progression to a combination of economic and ecological factors. We show that the ecological factors can be remarkably strong by using a spatially resolved, observationally-constrained, coupled macroecological-economic model to which we impose an idealized, globally homogeneous increase in catchability. The globally-uniform technology creep produces a spatial progression of fishing from high-to-low latitudes that is similar to observations, primarily due to the impact of temperature on ecosystem metabolism. In colder LMEs, low respiration rates allow the build-up of larger pristine standing stocks, so that high-latitude fisheries are profitable earlier, at lower levels of fishing technology. We suggest that these bioenergetic characteristics contributed significantly to the historical progression of this human-ecological system.